The Application of Mathematics to Calculation of Zakat in Home Sales - Syahputra, Rizki (Fakultas Keguruan dan Ilmu pendidikan (FKIP) Universitas Labuhan Batu, 2020)
Zakat is the name or designation of something that a person gives to those who are entitled to it, meaning zakat is one of the pillars of Islam that deals directly with property and social conditions. One of the forms of wealth to which the zakat should be issued is the wealth of commerce. Prof. Dr. Wahbah Zuhaili in his book, â€œAl-Fiqh al-Islam waadillatuhuâ€ describes the house when it comes to income / profit earned by renting / selling it is obligatory. The scholars explain that there is a zakat on real estate when selling a home. This is what was discussed at the second Muslim scholars in Cairo, that there is a zakat obligation on the profit or income of a home sale when it reaches nishab and is fulfilled when selling the house. Although he wants to buy a house again, he has to pay his charity first so that his wealth can be clean and be a blessing in life and in the hereafter.Keywords: Zakat, Mathematics,Home